Drug use by children in foster care placement at the Oaks Community, Limpopo Province : implications for social work practice - Mdhluli, Emmanuel (My University, 2015)
Please refer to the document
Thesis (M.A. (Social Work)) --University of Limpopo, 2015
Keywords: Foster care children; Drug use; Drud abuse; Social services; Foster children -- Care -- South Africa; Children -- Drug use -- South Africa